‘ Ughą jesedǔdla k’e’ - We work together : The impact of modern treaty First Nations in the Yukon working together on the implementation of the Final and Self-government Agreements - Badenhorst, Lisa (UiT Norges arktiske universitet, 2024)
This master’s thesis examines how modern treaty First Nations in the Yukon (MTFNYs) currently collaborate, and the potential impact of MTFNYs collaborating more on the implementation of the Final and Self-government agreements. It explores how MTFNYs, and non-Indigenous governments (Canada and Yukon) describe the implementation of the agreements; the benefits and obstacles to collaboration according to participants; and whether increased collaboration amongst MTFNYs could improve the implementation of the agreements. I argue that more collaboration would lead to increased resources for MTFNYs, an important need cited by participants for improved implementation. Collaboration would increase the power of MTFNYs, helping to offset the power imbalance between MTFNYs and non-Indigenous governments. This would improve negotiated outcomes for MTFNYs which leads to better implementation. Also, collaboration has indirect benefits such as improved relationships, increased trust and better solutions which could support improved implementation. And finally, when MTFNYs collaborate and use the court system it helps to improve implementation by balancing power between MTFNYs and non-Indigenous governments. Overall, participants saw collaboration as a useful tool to implement the agreements but saw many obstacles to collaboration. Only MTFNYs know whether the additional work of collaboration will overcome the obstacles leading to the desired results.